Calcinosis cutis secondary to facial acne vulgaris: A rare complication - Srimanta Kumar Sahu; Nikhil Gupta; Suruchi Vohra (Wolters Kluwer Medknow Publications, 2015)
Acne vulgaris is a common dermatological disease commonly affecting the adolescent and young adults. It is characterized by the presence of pleomorphic skin lesions such as comadones, papules, pustules, and nodules. The common complications are postacne hyperpigmentation and scarring causing psychological impact. Calcinosis cutis is the pathologic deposition of insoluble calcium salt in the skin and subcutaneous tissue. Calcinosis cutis following acne vulgaris is rarely reported in the literature. We report a case of calcinosis cutis in acne vulgaris in a 55-year-old man.